Are there differences between children's display of self-regulation and metacognition when engaged in an activity and when later reflecting on it? The complementary roles of observation and reflective dialogue. Issue 2 (2nd April 2016) - Robson, Sue
Abstract: Recent years have seen considerable growth of evidence that young children possess metacognitive and self-regulatory skills, alongside a view that some research tools, including observation and video-stimulated interviews, may provide better opportunities to see them. This paper examines possible differences in the evidence these two tools may afford. Data from 29 children aged 4–5 years in a London Reception class were analysed using a behavioural coding scheme. Overall, children were significantly more likely to display self-regulation and metacognition in post hoc interviews about an activity rather than during the activity. This was particularly so for metacognitive knowledge. Children were more likely to show regulatory aspects such as planning and monitoring during an activity, whilst evaluation was more evident in later discussion. Observations and video-stimulated interviews are suggested as valuable tools when combined with one another, offering complementary insights, and helping make children's learning more visible to both themselves and to adults.